2021
DOI: 10.1200/jco.20.00550
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Plus Ipilimumab for Treatment-Naïve Metastatic Uveal Melanoma: An Open-Label, Multicenter, Phase II Trial by the Spanish Multidisciplinary Melanoma Group (GEM-1402)

Abstract: PURPOSE This study aimed to assess the efficacy of the combination of nivolumab (nivo) plus ipilimumab (ipi) as a first-line therapy with respect to the 12-month overall survival (OS) in patients with metastatic uveal melanoma (MUM) who are not eligible for liver resection. METHODS This was a single-arm, phase II trial led by the Spanish Multidisciplinary Melanoma Group (GEM) on nivo plus ipi for systemic treatment-naïve patients of age > 18 years, with histologically confirmed MUM, Eastern Cooperative Onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 33 publications
12
153
0
1
Order By: Relevance
“…The ORR is in line with another previously published retrospective study reporting 11.6% to dual ICB [9] as well as to our previous report of 15.6% [10]. Two recently published prospective trials of the combination of ipilimumab with nivolumab in patients with metastatic UM showed results that slightly deviate [4,5]. Piulats et al enrolled only treatment-naïve patients and reported a lower OS (12.7 vs. 19.1 months), PFS (3 vs. 5.5 months), and ORR (11.5% vs. 18%) compared to Pelster et al, who enrolled patients with any number of prior treatments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ORR is in line with another previously published retrospective study reporting 11.6% to dual ICB [9] as well as to our previous report of 15.6% [10]. Two recently published prospective trials of the combination of ipilimumab with nivolumab in patients with metastatic UM showed results that slightly deviate [4,5]. Piulats et al enrolled only treatment-naïve patients and reported a lower OS (12.7 vs. 19.1 months), PFS (3 vs. 5.5 months), and ORR (11.5% vs. 18%) compared to Pelster et al, who enrolled patients with any number of prior treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Piulats et al reported a median number of two liver metastases (range 1-25) and a median size of the biggest liver metastases of 25 mm (range 10-90 mm); 78.8% of the patients had liver metastases and 57.7% presented with extrahepatic disease. The number of patients with exclusive liver metastases was not presented [4]. In comparison, Pelster et al reported that 49% of patients presented with hepatic and extrahepatic metastases, 31% with liver metastases only, and 20% with extrahepatic metastasis only [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Results from combination therapy with PV-10 and ICBs are awaited with interest. Complete results of the Spanish GEM-1402 study (ClinicalTrials.gov Identifier: NCT02626962) were recently published [ 75 ] ( Table 1 and Table 3 ). This phase II trial tested the efficacy of the combination of Nivolumab and Ipilimumab as first-line therapy in 52 patients with M-UM.…”
Section: Immune Checkpoint Inhibitors: Retrospective Real-world Studies and Clinical Trialsmentioning
confidence: 99%
“…Pembrolizumab showed a limited e cacy also in a prospective observational study, with a PFS of 3.8 months [16]. The association of Nivolumab and Ipilimumab allowed an overall survival (OS) of 12.7 months and a PFS of 3 months [17].…”
mentioning
confidence: 99%